(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the correlation between the level of automation of manufacturing processes and the amount of night work? Purpose: The purpose is to carry out an empirical study on the level of automation of manufacturing processes in larger Slovenian manufacturing companies and the amount of night work carried out by production workers and to determine whether a higher level of automation signifies a smaller amount of night work or to determine whether there is any statistically significant correlation between the said factors. Method: A quantitative survey was conducted on a sample of 116 medium-sized or large Slovenian manufacturing companies with at least 50 employees, to evaluate the level of automation of the entire production system through five groups of activities that occur within the production process. We compared the number of man-hours of production workers carried out during the night shift to the number of man-hours of production workers carried out throughout the whole workday. The estimated level of automation of each production system was then paired with the share of night work in relation to all days’ work, and the Pearson correlation coefficient was calculated. Results: The calculated correlation is of negative value, which means that the higher the level of automation of the manufacturing processes, the smaller the amount of the night work, but the absolute value is too low to speak of a statistically significant correlation. Organization: In relation to the automation of manufacturing processes, we have presented aspects and elements of automation that can help implement automation of manufacturing processes in an organization more effectively. In relation to night work, we have presented arguments as to why it makes sense for management to set a restriction on the amount of night work as a goal, and provide suggestions on how to pursue the said goal. Society: The research considers the automation of production processes as a potential solution for eliminating or limiting the amount of night work, as well as all the negative effects of night work on both the worker – an individual and also on his or hers social circle. Based on the findings, we have made proposals that can help eliminate or limit night work and thus affect the organization of working time and the quality of working life of an individual. Originality: The research addresses two substantively unrelated factors which have not yet had its potential correlation studied before. Limitations / further research: Research cannot be generalized to service organizations, nor can it be generalized to activities in manufacturing companies that do not take place within the production system. Researches on the automation and night work would also be useful to undertake based on other activities that are not manufacturing oriented, yet is such a form of work still absolutely necessary and inevitable, e.g. in healthcare, trade, police, media, military, etc.